Saturated shear strength behavior of granitic residual soil grade VI / Noraida Mohd Saim … [et al.] - Mohd Saim, Noraida; Md Noor, Mohd Jamaludin; Alias, Rohaya; Bachok, Mohd Fairuz; Wan Abdullah, Wan Zukri (2011)
Tropical residual soils are widespread in Malaysia due to its location in a hot and humid tropical region. More than 75% of the land area in Peninsular Malaysia is occupied by residual soil that formed by the weathering process of granitic, sedimentary and metasedimentary (metamorphic) rocks. Since the feature of tropical residual soil is prominent in engineering construction work such as highway cut-slopes, dam site excavations and is also widely used as construction fill materials for highway embankments, earth dam, and fill-platforms for housing development, the properties and the behavior of the residual soils needs to be investigated The main difficulty of the residual soils is associated with rainfall distribution and the effect of the infiltration of the surface run off on the earth. This is due to the slope failure cases on residual soil in the tropics are triggered by the infiltration of the surface run off that occurs during heavy rainstorm that caused damages and deaths. In this study, the shear strength characteristics of residual soil were assessed using consolidated drained (CD) triaxial tests for saturated soil specimens. Curve Surface Shear Strength Envelope Model (CSSEM) was used to interpret the test results. The test results shows that the failure envelope forms a non-linear shape at low stress levels that shows the soils exhibits drop in shear strength as effective stress approaches zero in saturated specimens. This is mean that shear strength vanished drastically as the soil gets closer to the ground surface and when it is wetted by the infiltrated water. Furthermore the application of Curve Surface Shear Strength Envelope Model (CSSEM) is useful to avoid the problem of overestimating and under estimating of shear strength behavior.